2022
DOI: 10.1142/s2010495222500312
|View full text |Cite
|
Sign up to set email alerts
|

The Asymmetric Effect of the Extreme Changes in the Economic Policy Uncertainty on the Exchange Rates: Evidence from Emerging Seven Countries

Abstract: This research has focused on examining the connection between uncertainties in economic policies and exchange rates. This research extends the literature to this field by analyzing the impact of small to large negative along with small to large positive variations in the economic policy uncertainty on the currency rates. For this purpose, this research uses the Granger causality in the quantile test and a newly constructed multiple asymmetric threshold nonlinear ARDL (MATNARDL) model. When a nonlinear ARDL mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The bootstrap technique is typically used to calculate P and F values by using a sampling number equivalent to 1000 times. However, other researchers like [ 44 ] and [ [45] , [46] , [47] ] conducted studies in advanced economics and found contradictory results. The possible reason for the differences in these results could be that those studies did not consider the various thresholds.…”
Section: Results Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bootstrap technique is typically used to calculate P and F values by using a sampling number equivalent to 1000 times. However, other researchers like [ 44 ] and [ [45] , [46] , [47] ] conducted studies in advanced economics and found contradictory results. The possible reason for the differences in these results could be that those studies did not consider the various thresholds.…”
Section: Results Discussionmentioning
confidence: 99%
“…They found that CO2 emissions increase due to increased foreign trade openness. [ 42 , 43 , 6 , 44 ]; and [ 29 ] conducted a study in the context of the US, Canada, and other advanced and developing countries. Their findings indicate that foreign trade openness causes a reduction in CO2 emissions.…”
Section: Results Discussionmentioning
confidence: 99%
“…Applying quantile regression, Archer et al (2022) revealed a significant connection between exchange rates and other variables like gold, cocoa, and oil prices in Ghana. Using the Granger causality in the quantile test and the multiple asymmetric threshold nonlinear ARDL model, Maydybura et al (2022) investigated the impact of Economic Policy Uncertainty (EPU) on exchange rates in the Emerging Seven (E7) countries. Applying EGARCH modelling, Van Der Westhuizen et al (2022) found that the stock market had influences on both the price and volatility of the foreign exchange market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on this, machine learning models began to be gradually used in exchange rate forecasting. In the existing literature, most studies proposed either the combination of linear models and machine learning models [7] or combinations of several machine learning algorithms for stacked optimization [8]. The research was biased towards improving the models from the technical point of view, but few studies were conducted to improve the models in terms of the characteristics of the financial market.…”
Section: Introductionmentioning
confidence: 99%